Open Access to Formal and Informal Learning: Theory and Practice the Open Discovery Space Portal: A Socially-Powered and Open Federated Infrastructure - Nikolas, A.; Sotiriou, S.; Zervas, P.; Sampson, Demetrios (2014)
During the past years, several open educational resources (OERs) initiatives around the world have been developed, which aim to create and share digital educational resources in the form of learning objects (LOs) that are openly licensed and available online for everyone to use. These initiatives have contributed in building and sustaining web-based repositories which are called learning object repositories (LORs). However, with many LORs implemented and maintained independently, valuable LOs are scattered over different LORs and it might be difficult for end users to easily access them. A suggested solution towards addressing this issue is to create infrastructures that enable the discovery and identification of LOs across different LORs. As a result, several federated infrastructures have been developed and are currently operating online. Within this context, a prominent European initiative has been launched, namely the Open Discovery Space (ODS) portal, which aims to (a) build a federated infrastructure for a super-repository on top of existing LORs and federated infrastructures and (b) provide social features for building and sustaining web-based educational communities and communities of best teaching practices from 2,000 European schools. To this end, the aim of this book chapter is to present the architecture of the ODS portal, as well as its current implementation and future plans.